Trusting the stock market - Michael Haliassos; Michael Reiter (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
We provide a new explanation to the limited stock market participation puzzle. In deciding whether to buy stocks, investors factor in the risk of being cheated. The perception of this risk is a function not only of the objective characteristics of the stock, but also of the subjective characteristics of the investor. Less trusting individuals are less likely to buy stock and, conditional on buying stock, they will buy less. The calibration of the model shows that this problem is sufficiently severe to account for the lack of participation of some of the richest investors in the United States as well as for differences in the rate of participation across countries. We also find evidence consistent with these propositions in Dutch and Italian micro data, as well as in cross country data.
urn:nbn:de:hebis:30-23396
Keywords: D1; D8; 330; Stock Market Participation; Trust; Portfolio Choice; Portfolio-Management; Anlageverhalten; Vertrauen; Schätzung; Italien; Niederlande